2021
DOI: 10.48550/arxiv.2112.00745
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Ferroelectric/paraelectric superlattices for energy storage

Hugo Aramberri,
Natalya S. Fedorova,
Jorge Íñiguez

Abstract: The polarization response of antiferroelectrics to electric fields is such that the materials can store large energy densities, which makes them promising candidates for energy storage applications in pulsed-power technologies. However, relatively few materials of this kind are known.Here we consider ferroelectric/paraelectric superlattices as artificial electrostatically-engineered antiferroelectrics. Specifically, using high-throughput second-principles calculations, we engineer PbTiO3/SrTiO3 superlattices t… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 40 publications
0
1
0
Order By: Relevance
“…Note also that one very recent work using high-throughput second-principles calculations (Aramberri et al, 2020) indicated that FE/paraelectric superlattices can be promising for energy storage as well. Other systems can also be investigated by first-principles-based effective Hamiltonian methods, or other ab initio techniques, in the near future for energy storage.…”
Section: Summary and Perspectivementioning
confidence: 99%
“…Note also that one very recent work using high-throughput second-principles calculations (Aramberri et al, 2020) indicated that FE/paraelectric superlattices can be promising for energy storage as well. Other systems can also be investigated by first-principles-based effective Hamiltonian methods, or other ab initio techniques, in the near future for energy storage.…”
Section: Summary and Perspectivementioning
confidence: 99%